Environmental elements in Maltese literature: Nature as metaphor in Dun Karm, the national poet - Friggieri, Oliver (Études sur la Région Méditerranéenne, 2014)
This essay seeks to establish the importance of the role played by the natural environment in Maltese romantic poetry. The landscape is seen as a physical as weil as a spirirual context within which various aspects of a poet's own existential anxiety are expressed and transformed into poetic images. Nature is treated on a double levél; it is both a reality and a metaphor, varying in significance according to a writer's inner state of being. The sea is equally recognised as a place and as a symbol since Maltese literature is greatly determined by the fact that life in Málta is intimately related to the sea, whilst references to the land necessarily recall the closeness to the ocean.